2012
DOI: 10.1021/ja304806j
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Chlorination of β-Keto Esters and Subsequent SN2 Displacement of Tertiary Chlorides: A Flexible Method for the Construction of Quaternary Stereogenic Centers

Abstract: Highly enantioselective chlorination of β-oxo esters and subsequent stereospecific substitution of tertiary chlorides are described. Enantioselective chlorination of β-keto esters and malonates was performed using a chiral Lewis acid catalyst prepared from Cu(OTf)(2) and the newly developed spirooxazoline ligand 2 to yield the desired α-chlorinated products with high enantioselectivity (up to 98% ee). Nucleophilic substitution of the resulting chlorides proceeded smoothly to afford a variety of chiral molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(69 citation statements)
references
References 46 publications
3
63
0
2
Order By: Relevance
“…We recently revealed that the S N 2 reaction of α-chloro-β-ketoesters proceeds smoothly to give the corresponding α-heteroatom-substituted-β-ketoesters with retained enantiopurity, despite the reaction taking place at a tertiary carbon atom2324. Encouraged by this result, we examined the nucleophilic substitution of α-chloroketone 2a (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We recently revealed that the S N 2 reaction of α-chloro-β-ketoesters proceeds smoothly to give the corresponding α-heteroatom-substituted-β-ketoesters with retained enantiopurity, despite the reaction taking place at a tertiary carbon atom2324. Encouraged by this result, we examined the nucleophilic substitution of α-chloroketone 2a (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…However, although the desired α-chloroketone 2a was obtained in good yield, the resulting enantioselectivity was poor. We also examined the reaction with a chiral Lewis acid catalyst prepared from a spiro pyridyl monooxazoline ligand L1 and copper(II) trifluoromethanesulfonate because it is known to catalyse electrophilic halogenation of β-ketoesters with high enantioselectivity222324. However, the decarboxylative chlorination of 1a using this catalyst also proceeded with poor enantioselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl (S)-2-Chloro-1-oxo-2,3-dihydro-1H-indene-2-carboxylate (7a) 11,15,24) Enantiomeric excess was determined by HPLC with ChiralPak AD-H column (hexane-2-propanol=95 : 5), flow rate=0.7 mL/min; λ=254 nm; t major =14.4 min, t minor =15.4 min.…”
Section: Experimental General Methods and Materialsmentioning
confidence: 99%
“…Several research groups have reported on the asymmetric chlorination of β-keto esters using metal catalysts. [6][7][8][9][10][11][12][13][14][15][16][17] Organocatalysis, meanwhile, has received considerable attention in the area of organic synthesis because, in comparison to reactions involving metal catalysts, it is an environmentally benign method. Synthetic methods for producing α-chlorinated compounds from β-keto esters using organocatalysts have also been developed.…”
mentioning
confidence: 99%
“…Chirale hypervalente Iodverbindungen und verschiedene Reaktionsbedingungen wurden in der Synthese von 2 i untersucht (Tabelle 4). [38] Die absolute Konfiguration der Reaktionsprodukte wurde mit bekannten Verbindungen verglichen, [39] und in jedem Fall wurde die R-Konfiguration der Stereozentren bestätigt. Die hçchste Se-Schema 2.…”
unclassified